2004
DOI: 10.1021/es030697z
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Tributyltin to Tin in Freshwater River-Bed Sediments Contaminated by an Organotin Release

Abstract: The largest documented release of organotin compounds to a freshwater river system in the United States occurred in early 2000 in central South Carolina. The release consisted of an unknown volume of various organotin compounds such tetrabutyltin (TTBT), tributyltin (TBT), tetraoctyltin (TTOT), and trioctyl tin (TOT) and resulted in a massive fish kill and the permanent closures of a municipal wastewater treatment plant and a local city's only drinking-water intake. Initial sampling events in 2000 and 2001 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Organotin residues were recently detected in sediments from several areas associated with ship traffic in Europe (Chiavarini et al 2003a;Nogueira et al 2003;Díez et al 2002Díez et al , 2006, Asia (Harino et al 2007;Nhan et al 2005), Oceania (Haynes and Loong 2002), and North America (Landmeyer et al 2004). In South America, ten studies determined organotins in sediments from 25 different sites associated to maritime activities ( Fig.…”
Section: Ots Contamination In Abiotic Matricesmentioning
confidence: 99%
“…Organotin residues were recently detected in sediments from several areas associated with ship traffic in Europe (Chiavarini et al 2003a;Nogueira et al 2003;Díez et al 2002Díez et al , 2006, Asia (Harino et al 2007;Nhan et al 2005), Oceania (Haynes and Loong 2002), and North America (Landmeyer et al 2004). In South America, ten studies determined organotins in sediments from 25 different sites associated to maritime activities ( Fig.…”
Section: Ots Contamination In Abiotic Matricesmentioning
confidence: 99%
“…Nevertheless the debutylation mechanism could be considered according to reported studies (Landmeyer et al 2004;Escalante et al 2009), as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…DBT concentration increases during incubation, reaching around 30 % of the original TBT concentration (1.5 mM). No MBT was The degradation rate constants (k) were calculated following pseudo-first order kinetics after 7 days of incubation (Stasinakis et al 2005;Brandsch et al 2001;Landmeyer et al 2004). The degradation rate constant (k) was 0.022 [day -1 ] and TBT half-life (t 1/2 ) in culture was 4.3 days.…”
Section: Resultsmentioning
confidence: 99%
“…In the marine environment, TBT soon abandoned the water column for sediment, the water distribution coefficient sediment (log 10 K oc ) is in the range 4.2-5.0 [4] given that the TBT molecule has a high specific mass, ∼ kg·L −1 at 20 • C [5], low solubility, <10 mg·L −1 at 20 • C and pH 7.0 [6] and the octanol/water distribution coefficient (log K ow ) is of ∼4.4 at pH 8 [7]. The result of this is that TBT's presence in water is extremely variable and is linked to the existence of active sources of contamination, whereas its duration in sediments is remarkably long.…”
Section: Characteristics Of Tbtmentioning
confidence: 99%